Systemic Inflammatory Reaction in Patients With Head and Neck Cancer—An Explorative Study - Astradsson, Thorsteinn; Sellberg, Felix; Berglund, David; Ehrsson, Ylva Tiblom; Laurell, Göran Frans Emanuel (Frontiers in Oncology, 2019)
Aim: To assess the longitudinal pattern of pro-inflammatory cytokines and growth factors in serum up to one year following treatment for head and neck cancer. Materials and Methods: Patients with newly diagnosed, curable head and neck cancer were included (n=30). The most common subsite was oropharynx (n=13) followed by oral cavity (n=9). Blood was drawn from all patients at regular intervals (before treatment, seven weeks after the start of the treatment, and at three months and one year after termination of treatment) and analyzed for cytokines (Il-1β, Il-2, Il-4, Il-5, Il-6, Il-8, Il-10, GM-CSF, TNF-α, and IFN- γ) and growth factors (G-CSF, FGF-2, EGF, and VEGF). Results: The time point of the peak level of pro-inflammatory cytokines was seven weeks after start of treatment which corresponded for the majority of patients with termination of radiotherapy or chemoradiotherapy. Patients undergoing chemoradiotherapy exhibited a significant increase of IL-1β, IL-6, and IL-10 at seven weeks as compared to pre-treatment levels. At one year after termination of treatment four patients experienced recurrence of disease while twenty-six patients were considered disease-free. The patients with recurrence had significantly higher levels of IL-1β, IL-6, IL-8, and IL-10 at seven weeks after the start of treatment than patients without recurrence. Correlated with T stadium patients with T3-T4 had higher levels of IL-1β and IL-8 than patients with T1-T2 seven weeks after the start of treatment. Conclusions: The observed immune response in this explorative study demonstrates that chemoradiotherapy may induce not only a local treatment effect on the immune system but also effects far outside the irradiated field. The result of the study indicates that analysis of a pro-inflammatory panel of cytokines in serum at seven weeks after the start of treatment could be of prognostic value in patients with head and neck cancer. Further study of a larger cohort could help identify patients at larger risk for recurrent disease with measurements of pro-inflammatory cytokines under and after treatment.